2019
DOI: 10.1007/s40091-019-00238-6
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of elastomeric seismic isolators for determining force–displacement curve from cyclic loading

Abstract: The ideal performance of seismic isolating systems during the past earthquakes has proved them to be very useful in protecting structures against earthquakes. The cyclic loading experimental tests are an important part in the process of completing the design of the isolators, yet they are very expensive and time consuming. Using the accurate analytical modeling of hysteresis tests and knowing the limitations and the amount of error of the finite elements model and its effect on designing the isolated structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It has been confirmed that the lead core provides an adequate level of energy dissipation [4,[10][11][12][13]. The numerical models for the analysis of the properties of a LRB were also developed [12,[14][15][16][17]. The seismic analysis of base isolated structures confirmed that the use of LRB has a favourable effect on the structural response [18][19][20].…”
Section: Figure 1 Characteristic Section and Basic Parts Of Lead Rubb...mentioning
confidence: 81%
“…It has been confirmed that the lead core provides an adequate level of energy dissipation [4,[10][11][12][13]. The numerical models for the analysis of the properties of a LRB were also developed [12,[14][15][16][17]. The seismic analysis of base isolated structures confirmed that the use of LRB has a favourable effect on the structural response [18][19][20].…”
Section: Figure 1 Characteristic Section and Basic Parts Of Lead Rubb...mentioning
confidence: 81%
“…These values are crucial for numerical analysis of the rubber hyper elastic properties. [114][115][116][117] 𝑈 = µ{ The strain energy function for the Marlow form are as follows:…”
Section: Materials Properties Used For Numerical Simulations and Anal...mentioning
confidence: 99%
“…Inserting a lead material into an isolation system is meant to give the hysteresis curve an elastic perfectly plastic behaviour [8]. The stress of lead material reaches the yield point under cyclic shear force at low tension stresses of 10 MPa and demonstrates a stable hysteric behaviour due to repeated yields under cyclic load [19]. The parameters of the lead material used in this study are listed in Table 3.…”
Section: Lead Materialsmentioning
confidence: 99%
“…Isotropic, elastic, isothermal, and incompressible behaviour can be used to model such materials. The time and loading frequency have no effect on their behaviour during the test [19]. The ABAQUS software [27] has a number of hyperelastic material types, each of which defines the strain energy function differently.…”
Section: Rubber Materialsmentioning
confidence: 99%
See 1 more Smart Citation